Optimizing the utilisation of EV light goods vehicles for supermarket delivery services - Wallom, DCH; Zhang, C (European Council for an Energy Efficient Economy, 2022)
With the rise of online grocery shopping, a centralized delivery model has the potential to improve sustainability. Growing demand though brings challenges to grocery retailers’ net-zero targets with many retailers’ sustainability plans detailing the transition to electric vehicles (EV) within logistics as essential. In this study, a feasibility analysis on replacing internal combustion engine vehicles (ICEV) with EVs for Sainsbury's grocery delivery business in Oxfordshire was conducted. As grocery delivery has stricter timing requirements and considerations must be made for EV charging and load management, several methodologies were proposed and used in simulations.